2011
DOI: 10.2337/dc10-1447
|View full text |Cite
|
Sign up to set email alerts
|

Improved Glycemic Control Without Hypoglycemia in Elderly Diabetic Patients Using the Ubiquitous Healthcare Service, a New Medical Information System

Abstract: OBJECTIVETo improve quality and efficiency of care for elderly patients with type 2 diabetes, we introduced elderly-friendly strategies to the clinical decision support system (CDSS)-based ubiquitous healthcare (u-healthcare) service, which is an individualized health management system using advanced medical information technology.RESEARCH DESIGN AND METHODSWe conducted a 6-month randomized, controlled clinical trial involving 144 patients aged >60 years. Participants were randomly assigned to receive routine … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
194
2
5

Year Published

2012
2012
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 180 publications
(205 citation statements)
references
References 23 publications
4
194
2
5
Order By: Relevance
“…The strength of the evidence for short-term mortality was graded as moderate, given that results were precise, direct, and had low risk of bias (Table 2). Table 7), 4,21,49,61,62,69,[72][73][74][75][76][77][78][79][80][81][82][83] showing no clear differences between groups in hypoglycemia. The strength of evidence was graded as low, given the inconsistency and imprecision of the results (Table 2).…”
Section: Safetymentioning
confidence: 99%
See 3 more Smart Citations
“…The strength of the evidence for short-term mortality was graded as moderate, given that results were precise, direct, and had low risk of bias (Table 2). Table 7), 4,21,49,61,62,69,[72][73][74][75][76][77][78][79][80][81][82][83] showing no clear differences between groups in hypoglycemia. The strength of evidence was graded as low, given the inconsistency and imprecision of the results (Table 2).…”
Section: Safetymentioning
confidence: 99%
“…Most studies reported hypoglycemia as total hypoglycemic events [75][76][77] (N=5) or p a r t i c i p a n t s e x p e r i e n c i n g h y p o g l y c e m i a ( N = 8). 61,62,69,73,74,78,80,82 Hypoglycemic outcomes were defined heterogeneously, with some studies based on self report 4,21,62,72,73,77,82 and others on glucose readings. 74,76,78 Twelve of the 18 studies reported measures of variability.…”
Section: Safetymentioning
confidence: 99%
See 2 more Smart Citations
“…The mean age of all participants ranged from 46 to 71 years. Ten studies (13,14,15,16,17,18,19,20,21,22) limited inclusion criteria to participants 1240 records identified through searches 899 records after duplicates removed 800 excluded based on abstracts.…”
Section: Study Characteristicsmentioning
confidence: 99%